EFEKTIVITAS PELAKSANAAN PROGRAM KELUARGA BERENCANA DALAM PENGENDALIAN JUMLAH PENDUDUK DI PROVINSI RIAU - Ester Vinanita Cristiana; Harlen Harlen; Any Widayatsari (Program Studi Pendidikan Ekonomi Universitas Riau, 2021)
The purpose of this study was to analyze the effectiveness of the family planning program in controlling the population in Riau Province. The data used is the performance accountability report of the representative government agencies of the Riau Province BKKBN from 2015 to 2019. The analysis was carried out using a descriptive method, using a targeted approach, namely an approach that measures the level of success of an activity based on the goals achieved by a program compared to the targets to be obtained. The results of the analysis show that the family planning program is very effective in controlling the population in Riau Province, which is reflected in the increasing trend of contraceptive acceptors and the decreasing population growth rate, which means that the family planning program can control the population growth rate.